PENGARUH JENIS BAHAN PENYALUT TERHADAP EFISIENSI ENKAPSULASI DAN SIFAT FISIKOKIMIA EKSTRAK MEDINILLA SPECIOSA DENGAN TEKNIK FOAM MAT DRYING - Boby Pranata; Dwi Indah Permata Sari; Harumi Sujatmiko; Ina Permata Sari; Tri Nurmaseli (Jurnal Pangan dan Gizi, 2025)
This study aimed to examine the effect of various coating materials on the encapsulation efficiency and physicochemical characteristics of Medinilla speciosa (parijoto) fruit extract powder dried using the foam mat drying method. Parijoto extract was encapsulated using three coating materials, namely maltodextrin (MDE), gum arabic (ABG), and whey protein isolate (WPI), either singly or in combination. The parameters analyzed included anthocyanin encapsulation efficiency, total anthocyanin content, phenolic and flavonoid compounds, antioxidant activity, water content, water activity, pH value, solubility, and product yield. The results showed that the ABG:WPI combination formulation produced the highest encapsulation efficiency (33.58%) and higher bioactive compound content and antioxidant activity compared to other formulations. MDE coating significantly contributed to increasing yield, solubility, and decreasing water content and water activity. The combination of coating materials was proven to produce a positive synergy in maintaining the stability of bioactive components while improving the physical characteristics of the final product. This study indicates that the combination of ABG and WPI is the optimal coating formulation for the encapsulation application of bioactive compounds from parijoto fruit in the development of powder-based functional food products